Breeding properties and cytological characteristics of interspecific hybrids between the Ussuri plum and bullace - D. S. Garapov; O. V. Mochalova (Труды по прикладной ботанике, генетике и селекции)
Background. Interspecific hybrids between the Ussuri plum (Prunus salicina subsp. ussuriensis (Koval. et Kost.) Erem.) and bullace (P. domestica subsp. insititia (Jusl.) Schneid.) were studied to discover causes of their low yields. A possibility is shown to use interspecific diploid hybrids in plum breeding for resistance to asphyxiation in snow-rich regions of Siberia.   Materials and methods. The research materials included interspecific hybrids: Ayskaya (2n = 16), six Ayskaya seedlings (2n = 16, 24), and TSG No. 8 (2n = 32); Ussuri plum cv. ‘Altayskaya Yubileynaya’ (2n = 16), and bullace 18-119 (2n = 48). The research was conducted in 2004–2023 in the forest-steppe zone of the Ob river region in Altai. Conventional cytological andcultivar-testing methods were used.   Results and conclusion. The yield of the Ayskaya and TSG No. 8 interspecific hybrids strongly depended on mean daily temperatures during blossoming (r = 0.77 ± 0.26 and r = 0.74 ± 0.27, respectively) when compared to the Ussuri plum. Fruit trait segregation in the Ayskaya seedlings was specific to diploid plums – variations in fruit weight (5.6–27.6 g), skin color (violet, claret, red, and yellow), and flesh color (yellow, red, and green). Most fruit traits of the seedlings were similar to those of their maternal form. The content of polyaperturate pollen in polyploids (25.0–37.9 %) was much higher than in diploids (less than 1.4 %), which means that this trait makes it possible to identify polyploids in the progenies of interspecific plum hybrids. Diploid form 12-04-309 (pollen fertility: 45.9%) was selected as a source of asphyxiation resistance for diploid plum breeding, and tetraploid form TSG No. 8 (pollen viability: 24.2 %) for hybrid blackthorn breeding.